Effect of Packaging Materials and Pre-treatments on Infestation of Stored Arhar - Singh, A; Gupta, D K (Journal of Agricultural Engineering, 2002)
Infestation on dhal prepared from untreated, NaHC03 treated and oil treated pigeonpea grains was studied for eight months under various storage conditions. Dhal samples were stored in different packaging materials (polythene, polylined and jute bags) at 9% and 12% initial moisture content. Effect of fumigation ( ethylene-di-bromide) was also investigated. For dhal samples, polythene bags had the lower level of infestation as compared to polylined and jute bags. NaHC03 treatment and fumigation could reduce the level of infestation upto some extent. For dhal samples, rice moth and weevils were the main infesting insects.